Direct monitoring of spin transitions in a dinuclear triple-stranded helicate iron(ii) complex through X-ray photoelectron spectroscopy. Issue 8 (31st January 2018) - Li, Li; Craze, Alexander R.; Akiyoshi, Ryohei; Tsukiashi, Asami; Hayami, Shinya; Mustonen, Outi; Bhadbhade, Mohan M.; Bhattacharyya, Saroj; Marjo, Christopher E.; Wang, Yun; Lindoy, Leonard F.; Aldrich-Wright, Janice R.; et al.
Abstract : VT-XPS shows that the spin behaviour is reversible between the HS and LS states in a new dinuclear helicate iron(ii ) complex. Abstract : A dinuclear helical iron(ii ) complex of a new ditopic thiazolylimine ligand (L ) has been synthesised via supramolecular assembly. The resulting dinuclear helical cylinder [Fe2 L3 ]·4BF4 was investigated by variable temperature X-ray crystallography, ESI high resolution mass spectrometry, CHN analysis, FT-IR and UV-Vis spectroscopy. The nature of the spin transition was investigated by magnetic susceptibility measurements, and confirmed by VT-SCXRD and X-ray photoelectron spectroscopy. [Fe2 L3 ]·4BF4 displays a complete spin transition with a gradual-abrupt character at T 1/2 = 348 K and represents a new example of a dinuclear iron(ii ) complex exhibiting a spin transition at high temperature. Both VT-SCXRD and XPS measurements show excellent correlation with the magnetic susceptibility experiments, demonstrating the power of XPS not just to confirm, but also to clearly follow the spin-state transition in Fe(ii ) SCO complexes.